Pengaruh Terapi Antituberkulosis Terhadap Pertumbuhan Penderita Tuberkulosis Anak di Kota Jambi - Rahman, Ave Olivia; Ayu, Esa Indah; ., Miftahurrahmah (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background: Tuberculosis (TB) is still a major health problem in the world. Indonesia is in the top fifth contributing to the highest number of TB cases in the world. Subdit TB Depkes RI 2000-2010 reported that Jambi is one of the province with high proportion of pediatric TB, 5,2%. Tuberculosis can affect the children’s growth. Combination of antituberculosis drugs are used in the therapy of tuberculosis. Some studies show that the antituberculosis drugs cause side effects. Methods: This is an observational research with cohort prospective design. Subjects are patients who diagnosed as pediatric TB in RSUD Raden Mattaher, Puskesmas Putri Ayu, Puskesmas Simpang IV Sipin and PPTI Jambi. Subjects have given informed consent. The recruitment of subject from July until September 2014 and followed until two month therapy. The primary data from interview and weight measurement, secondary data from patients’ medical records. Results: Total subjects are 24 patients. The 87,5% subjects diagnosed as TB pulmonary and 12,5% subjects diagnosed as TB extrapulmonary (meningitis TB, spondylitis TB and scrofuloderma). About 54,2% subjects are above 4 years old. The location of patients’ adresses are 20,8% from Kecamatan Jambi Timur subdistrict, followed respectively from Telanai, Kota baru, Pelayangan, Jelutung and Danau Teluk. The 79,2 % subjects have close contact with positive TB adult patients. About 8,3% subjects experience loss of appetite, 4,1 % experience naussea during therapy with antitubercular drugs. Based on weight/age criteria, about 91,7 % subjects are categorized malnutrition and 8,3 % are well nutrition before therapy. There are different significantly increasement of body weight before, after 1 month and 2 month of therapy (p<0,05). Conclusion: There are significantly increasement of body weight before, after 1 month and 2 month of therapy (p<0,05). Keywords: Pediatric TB, growth weight, side effects